ESTABLISHING SALES ETHICS AND ITS IMPACT ON CUSTOMERS IN URBAN BANKING ORGANIZATIONS - Widiya Avianti; Pitaloka, Endang (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
To determine how sales incentive systems impact salespeople's ethical behavior, consumer perceptions of the firm, and consumer perceptions of banking products, an investigation was conducted at bank financial institutions. The study was conducted in Indonesian cities. A total of 231 people were surveyed who were aware of the sales force reward system through purposive sampling method. The results of data processing using structural equation models show that the salesperson reward system affects the ethical behavior of salespeople. As this study finds, there is a relationship between marketing management and human resource management. This is the only independent variable related to human resource management. The two variables are the salesperson ethical behavior system and the salesperson reward system, so the strategy of creating consumer perception depends on the company's HR management elements.